Comparison of out-of-field photon doses in 6 MV IMRT and neutron doses in proton therapy for adult and pediatric patients - Athar, Basit S (2010)
The purpose of this study was to assess lateral out-of-field doses in 6 MV IMRT (intensity modulated radiation therapy) and compare them with secondary neutron equivalent dose contributions in proton therapy. We simulated outof-field photon doses to various organs as a function of distance, patient's age, gender and treatment volumes based on 3, 6, 9 cm field diameters in the head and neck and spine region. The out-of-field photon doses to organs near the field edge were found to be in the range of 2, 5 and 10 mSv Gy(−1) for 3 cm, 6 cm and 9 cm diameter IMRT fields, respectively, within 5 cm of the field edge. Statistical uncertainties calculated in organ doses vary from 0.2% to 40% depending on the organ location and the organ volume. Next, a comparison was made with previously calculated neutron equivalent doses from proton therapy using identical field arrangements. For example, out-of-field doses for IMRT to lung and uterus (organs close to the 3 cm diameter spinal field) were computed to be 0.63 and 0.62 mSv Gy(−1), respectively. These numbers are found to be a factor of 2 smaller than the corresponding out-of-field doses for proton therapy, which were estimated to be 1.6 and 1.7 mSv Gy(−1) (RBE), respectively. However, as the distance to the field edge increases beyond approximately 25 cm the neutron equivalent dose from proton therapy was found to be a factor of 2–3 smaller than the out-of-field photon dose from IMRT. We have also analyzed the neutron equivalent doses from an ideal scanned proton therapy (assuming not significant amount of absorbers in the treatment head). Outof-field doses were found to be an order of magnitude smaller compared to out-of-field doses in IMRT or passive scattered proton therapy. In conclusion, there seem to be three geometrical areas when comparing the out-of-target dose from IMRT and (passive scattered) proton treatments. Close to the target (in-field, not analyzed here) protons offer a distinct advantage due to the lower integral dose. Out-of-field, but within approximately 25 cm from the field edge, the scattered photon dose in IMRT turned out to be roughly a factor of 2 lower than the neutron equivalent dose from proton therapy for the fields considered in this study. At larger distances to the field (beyond~ 25 cm), protons offer an advantage, resulting in doses that are roughly a factor of 2–3 lower.